The comparison study of the treatment of posterior capsule opacity after cataract surgery between 2 types of intraocular lens - ประเสริฐ, วิวัฒน์; จันทร์ลลิต, วรัทพร; โชติขจรเกียรต, ณิชาบูล (Journal of Medicine and Health Sciences, 2019)
Abstract Posterior capsular opacification is the most common long term complication after cataract surgery. The most important factors causing posterior capsular opacification are material and design of the intraocular lens. Hydrophilic acrylic has higher rates in posterior capsular opacification and Nd:YAG capsulotomy rate compared to PMMA, silicone and hydrophobic acrylic material types. Squared-edge intraocular lens reduced the posterior capsular opacification compared to round-edge intraocular lens. This study was to compare percentage of posterior capsular opacification and Nd:YAG capsulotomy rates between the most frequent intraocular lens used in Maha Chakri Sirindhorn Medical Center: PMMA (round edge, EZE55, Baush & Lomb) and hydrophilic acrylic (square edge, Akreos MI60, Baush & Lomb).All patients underwent phacoemulsification and implantation of PMMA and hydrophilic acrylic intraocular lens from 2009-2012 with a minimum of 3 years’ follow up. Cases with Nd:YAG capsulotomy were included in the study. From a total of 1624 cataract operations, twenty-four eyes (3.66%) implanted with hydrophilic acrylic Akreos MI60 underwent Nd:YAG capsulotomy by 18 months after cataract surgery. Twenty-nine eyes (7.12%) implanted with PMMA EZE55 underwent Nd:YAG capsulotomy by 36 months after surgery. The risk of time to capsulotomy were 8.31 (95% CI, 3.54-19.49) comparing hydrophilic acrylic Akreos MI60 to PMMA EZE55. Finally hydrophilic acrylic (Akreos MI60) has a higher risk to capsulotomy at early postoperative period compare to hydrophobic, EZE55.